Foot and Mouth Disease (FMD) among Animals in Nepal - Parajuli, Pratiksha; Pandit, Sudiksha; Kaphle, Krishna (International Journal of Applied Sciences and Biotechnology, 2020)
Foot and Mouth disease (FMD) is a highly contagious viral disease, affecting all domestic as well as wild cloven-hoofed animals caused by Apthovirus of Picornaviride family. FMD is endemic in Nepal causing substantial economic losses to livestock industry mainly cattle and buffalo, directly by decreasing the production and change in herd structure, and indirectly losses by cost of FMD control. The predominant serotype responsible for endemic outbreak of FMD in Nepal is ‘O’ however serotypes ‘A’ and ‘Asia-1’ have also been detected. Peak level of occurrence is noticed during pre-monsoon (April - May) and post-monsoon (Oct-Nov) period, however it occurs throughout the year. Movement of animals within the country mainly during festival season, illegal trading of livestock between Nepal and India because of open border, poor knowledge about the disease among farmers, high cost of treatment and control, lack of strict quarantine practices are the major factors contributing to high frequency of outbreak. Cattles were most frequently affected followed by buffalo, goat, sheep and pig. The objective of this paper is to evaluate the current scenario of FMD in Nepal, its transmission, diagnostic approaches and prevention and control measures. This paper is based on review of different articles from various journals, magazines, epidemiological bulletin, and reports from government of Nepal. The present approach to control this disease is through the vaccination of animal by imported multivalent vaccines. Vaccinations based on the matching of a vaccine strain to a field strain can be a better approach. Int. J. Appl. Sci. Biotechnol. Vol 8(1): 7-13